Revisiting global fossil fuel and biofuel emissions of ethane. Issue 4 (28th February 2017) - Tzompa‐Sosa, Z. A.; Mahieu, E.; Franco, B.; Keller, C. A.; Turner, A. J.; Helmig, D.; Fried, A.; Richter, D.; Weibring, P.; Walega, J.; Yacovitch, T. I.; Herndon, S. C.; et al.
Abstract: Recent measurements over the Northern Hemisphere indicate that the long‐term decline in the atmospheric burden of ethane (C2 H6 ) has ended and the abundance increased dramatically between 2010 and 2014. The rise in C2 H6 atmospheric abundances has been attributed to oil and natural gas extraction in North America. Existing global C2 H6 emission inventories are based on outdated activity maps that do not account for current oil and natural gas exploitation regions. We present an updated global C2 H6 emission inventory based on 2010 satellite‐derived CH4 fluxes with adjusted C2 H6 emissions over the U.S. from the National Emission Inventory (NEI 2011). We contrast our global 2010 C2 H6 emission inventory with one developed for 2001. The C2 H6 difference between global anthropogenic emissions is subtle (7.9 versus 7.2 Tg yr −1 ), but the spatial distribution of the emissions is distinct. In the 2010 C2 H6 inventory, fossil fuel sources in the Northern Hemisphere represent half of global C2 H6 emissions and 95% of global fossil fuel emissions. Over the U.S., unadjusted NEI 2011 C2 H6 emissions produce mixing ratios that are 14–50% of those observed by aircraft observations (2008–2014). When the NEI 2011 C2 H6 emission totals are scaled by a factor of 1.4, the Goddard Earth Observing System Chem model largely reproduces a regional suite of observations, with the exception of the central U.S., where it continues to underpredict observed mixing ratios in the lower troposphere. We estimate monthly mean contributions of fossil fuel C2 H6 emissions to ozone and peroxyacetyl nitrate surface mixing ratios over North America of ~1% and ~8%, respectively. Key Points: We present a global C2 H6 emission inventory and simulate C2 H6 abundances for the year 2010 by using the GEOS‐Chem model Northern Hemisphere fossil fuel sources represent 95% of global fossil fuel emissions and half of total global C2 H6 emissions NEI 2011 C2 H6 emissions produce C2 H6 mixing ratios that are 14–50% of those observed by recent aircraft observations across the U.S.